Regulation of bile acids and their receptor FXR in metabolic diseases - Li, Yao; Wang, Lulu; Yi, Qing; Luo, Linsong; Xiong, Yuxia (Frontiers in Nutrition, 2024)
High sugar, high-fat diets and unhealthy lifestyles have led to an epidemic of obesity and obesity-related metabolic diseases, seriously placing a huge burden on socio-economic development. A deeper understanding and elucidation of the specific molecular biological mechanisms underlying the onset and development of obesity has become a key to the treatment of metabolic diseases. Recent studies have shown that the changes of bile acid composition are closely linked to the development of metabolic diseases. Bile acids can not only emulsify lipids in the intestine and promote lipid absorption, but also act as signaling molecules that play an indispensable role in regulating bile acid homeostasis, energy expenditure, glucose and lipid metabolism, immunity. Disorders of bile acid metabolism are therefore important risk factors for metabolic diseases. The farnesol X receptor, a member of the nuclear receptor family, is abundantly expressed in liver and intestinal tissues. Bile acids act as endogenous ligands for the farnesol X receptor, and erroneous FXR signaling triggered by bile acid dysregulation contributes to metabolic diseases, including obesity, non-alcoholic fatty liver disease and diabetes. Activation of FXR signaling can reduce lipogenesis and inhibit gluconeogenesis to alleviate metabolic diseases. It has been found that intestinal FXR can regulate hepatic FXR in an organ-wide manner. The crosstalk between intestinal FXR and hepatic FXR provides a new idea for the treatment of metabolic diseases. This review focuses on the relationship between bile acids and metabolic diseases and the current research progress to provide a theoretical basis for further research and clinical applications.